2017
DOI: 10.1016/j.jgr.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of fermented black ginseng against cisplatin-induced nephrotoxicity in rats

Abstract: BackgroundFermented black ginseng (FBG) is processed ginseng by the repeated heat treatment and fermentation of raw ginseng. The protective effect and mechanism of FBG on cisplatin-induced nephrotoxicity was investigated to evaluate its therapeutic potential.MethodsThe free radical scavenging activity of FBG was measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH). In addition, the protective effect against cisplatin-induced renal damage was tested in rats. FBG was orally administered every day at a dose of 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Antioxidant capacity enhancement was alleged to those microbes convert several components in food or substrat and changes sugar to alcohol and lactic acid which can increase bioactivity of the components (Bae et al 2004;Trint et al 2007). Jung et al (2017) mentioned that antioxidant capacity of red ginseng extract by the probiotic Lactobacillus plantarum KCCM 11613P. Those phenomenon was similar to this research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Antioxidant capacity enhancement was alleged to those microbes convert several components in food or substrat and changes sugar to alcohol and lactic acid which can increase bioactivity of the components (Bae et al 2004;Trint et al 2007). Jung et al (2017) mentioned that antioxidant capacity of red ginseng extract by the probiotic Lactobacillus plantarum KCCM 11613P. Those phenomenon was similar to this research.…”
Section: Discussionsupporting
confidence: 85%
“…Research in other raw plant material showed that the total phenolic content in black ginseng fermented by S. cerevisiae was higher than that of raw ginseng and black ginseng (Jung et al 2017). Jhan et al (2015) reported that the total phenolic content increased after fermentation, when red beans were fermented by B. subtilis and L. delbrueckii sub sp.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is known to demonstrate toxic effects on the renal tubule, vasculature, and glomeruli. It results in structural damage to the kidney and consequently increases creatinine and urea in blood [37][38][39]. Panaxynol treatment reduced the serum creatinine and BUN in mice with cisplatin-induced kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Bioconversion has also been applied to food wastes such as wastes from coffee beans, fruit, onion, vegetables and wheat bran to generate renewable energy (Uckun et al, 2014). Bioconverted ginseng and ginsenosides have focused on evaluating their beneficial effects because they can prevent more effectively hypertension, regulate oxidative stress and prevent cancer cell growth than non-bioconverted ones Jung et al, 2017). Bioconverted ginseng and ginsenosides have focused on evaluating their beneficial effects because they can prevent more effectively hypertension, regulate oxidative stress and prevent cancer cell growth than non-bioconverted ones Jung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many researchers reported on the bioconversion of fresh ginseng, red ginseng and specific ginsenosides using microorganisms, purified enzymes and recombinant enzymes (Cui et al, 2013;Huq et al, 2014;Jo et al, 2014;Lee et al, 2014). Bioconverted ginseng and ginsenosides have focused on evaluating their beneficial effects because they can prevent more effectively hypertension, regulate oxidative stress and prevent cancer cell growth than non-bioconverted ones Jung et al, 2017). In addition, several studies on microbial bioconversion pathway of ginsenoside have been conducted using HPLC assay (Dong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%